Development of competency model for quality specialists. (20th May 2009) - Chang, Dong-Shang; Chen, Hsuan-Yueh; Ho, Chin-Tsang; Lu, Iuan-Yuan
This article focuses on the development of a competency model of quality specialists. First, it provides a competency model for quality specialists to apply several qualitative methods to build a model. Second, after formally conducting tests with scales, use an exploratory factor analysis to refine and to construct a validity of the scale. The results show three major competency groups among quality specialists of small and medium enterprises. Finally, a confirmatory factor analysis is applied to test the goodness of the fitness of the proposed competency model. The practical application to recruit, serve as educational training and career development for quality specialists.